Mitochondrial plasticity supports proliferative outgrowth and invasion of ovarian cancer spheroids during adhesion - Grieco, Joseph P.; Compton, Stephanie L. E.; Bano, Nazia; Brookover, Lucy; Nichenko, Anna S.; Drake, Joshua C.; Schmelz, Eva M. (Frontiers in Oncology, 2023)
Ovarian cancer cells aggregate during or after exfoliation from the primary tumor to form three-dimensional spheroids. Spheroid formation provides a survival advantage during peritoneal dissemination in the nutrient and oxygen-depleted conditions which is accompanied by a suppressed metabolic phenotype and fragmented mitochondria. Upon arrival to their metastatic sites, spheroids adhere to peritoneal organs and transition to a more epithelial phenotype to support outgrowth and invasion. In this study, we investigated the plasticity of mitochondrial morphology, dynamics, and function upon adhesion and mimicked reoxygenation (change of culture conditions from hypoxia and low glucose to normoxia with high glucose levels) using our slow-developing (MOSE-L) and fast-developing (MOSE-LTICv) ovarian cancer models. Independent of culture conditions, all spheroids adhered to and began to grow onto the culture plates. While the bulk of the spheroid was unresponsive, the mitochondrial morphology in these outgrowing cells was indistinguishable from cells growing in monolayers, indicating that mitochondrial fragmentation in spheroids was indeed reversible. This was accompanied by an increase in regulators of mitobiogenesis, PGC1, mitochondrial mass, and respiration. Reoxygenation increased migration and invasion in both cell types but only the MOSE-L responded with increased proliferation to reoxygenation. The highly aggressive phenotype of the MOSE-LTICv was characterized by a relative independence of oxygen and the preservation of higher levels of proliferation, migration and invasion even in limiting culture conditions. Further, the outgrowth in these aggressive cells relies mostly on proliferation while the MOSE-L cells both utilize proliferation and migration to achieve outgrowth. Suppression of proliferation with cycloheximide impeded aggregation, reduced outgrowth and invasion via repression of MMP2 expression and the flattening of the spheroids. Our studies indicate that the fragmentation of the mitochondria is reversible upon adhesion. The identification of regulatory signaling molecules and pathways of these key phenotypic alterations that occur during primary adhesion and invasion is critical for the identification of druggable targets for therapeutic intervention to prevent aggressive metastatic disease.